2012
DOI: 10.1007/s00213-012-2729-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saffron on fluoxetine-induced sexual impairment in men: randomized double-blind placebo-controlled trial

Abstract: Saffron is a tolerable and efficacious treatment for fluoxetine-related erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 42 publications
2
61
0
2
Order By: Relevance
“…[65] Men and women treated with Selective Serotonin Reuptake Inhibitors (SSRIs) experienced beneficial effects on their sexual function by simultaneous administration of saffron extract. [111] Moreover, saffron seemed to ameliorate the sexual arousal, lubrication and pain domains of fluoxetinerelated sexual dysfunction in women. [112] However, there is no clear clinical evidence regarding neither the aphrodisiac effect of saffron nor its effectiveness on erectile dysfunction in males.…”
Section: Other Possible Applicationsmentioning
confidence: 99%
“…[65] Men and women treated with Selective Serotonin Reuptake Inhibitors (SSRIs) experienced beneficial effects on their sexual function by simultaneous administration of saffron extract. [111] Moreover, saffron seemed to ameliorate the sexual arousal, lubrication and pain domains of fluoxetinerelated sexual dysfunction in women. [112] However, there is no clear clinical evidence regarding neither the aphrodisiac effect of saffron nor its effectiveness on erectile dysfunction in males.…”
Section: Other Possible Applicationsmentioning
confidence: 99%
“…In Iranian's traditional medicine, ointments containing saffron are used to treat hot palpitation of heart [4]. Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Saffron aqueous extract 30 mg daily for 12 weeks could prevent metabolic syndrome and increases in blood glucose in schizophrenia patients on olanzapine treatment [48]. Saffron 15 mg twice daily for 4 weeks could significantly improve fluoxetine-related sexual dysfunction among both female and male patients with major depressive disorder who were stabilized on fluoxetine [49, 50]. …”
Section: Resultsmentioning
confidence: 99%